(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background : Pregnancy-also known as gestation is the time during which one or more offspring develops inside a woman. A multiple pregnancy involves more than one offspring, such as with twins. Pregnancy usually occurs by sexual intercourse, but can occur through assisted reproductive technology protedures. To assess the efficacy of oral Nifedipine and I/V Labetalol for lowering BP in severe PIH after 28 weeks of pregnancy. Materials and methods: In this study 100 subjects were selected with severe pregnancy induced hypertension as per inclusion criteria. After taking informed written consent they were randomly allocated into two groups, A & B. Group A received initially tablet nifedipine 10 mg orally with repeated doses of 20 mg every 20 minutes upto five doses while Group B received intravenous labetalol 20 mg initially followed by escalating doses of 40, 80, 80 and 80 mg every 20 minutes until the therapeutic goal blood pressure Systolic £ 150 mmHg & diastolic £ 100 mmHg was achieved. Primary outcomes were the time interval and the number of doses needed to achieve a blood pressure of £ 150/100 mmHg, Secondary outcomes were fetomaternal safety, efficacy and side effects of both drugs. The outcomes were recorded in a preformed data collection sheet. All the data were analyzed by computer based software SPSS version 19 (SPSS Inc, Chicago, IL, USA). P <0.05 at 95% level was taken as statistically significant. Results: A total of 100 patients of different ages with mean age of 27.41 years were taken in the study. Primi patients were more in Group A the Group B and mode of delivery was commonly caesarian section (66% vs 78%) in both groups. Proportion of target BP achievement were 100% in Group A and it was 72% in Group B. Need of drug dose and time of reduction was found significantly less among Group A women. Change of mean ± SD, SBP was more rapid in Group A ( 174.90 ± 20.01 vs 158.40 ± 11.13) women who were on Group A oral nifedipine than Group B ( 179.80 ± 16.54 vs 167.40 ± 15.02) i/v labetalol group after first dose. It was same for DBP also. Need of mean dose were less in group A than Group B (1.72 vs 3.30) also total time needed to achieve target BP was less in Group A (34.40 vs 66.0 mins). There was no need of doses exceeding third dose who were on oral nifidipine than i/v labetolol. Both maternal and fetal heart rate was not influenced by both the drugs. Side effects of drugs were found more in Group B (8% vs 4%) and fetal death also more common in there (8% vs 16%). Value of APGAR scores was found higher both at 1 minute and at 5 minutes among Group A neonates than Group B. Significant urine output volume was found in Group A patients than Group B at first hour. Conclusion: Oral nifedipine and intravenous labetalol both the regimens are found to be effective in the management of severe PIH. But Nifidipine lowers blood pressure more rapidly with fewer doses with minimum fetomaternal side-effects. Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 55-61